Optimization of thermal systems based on finite-time thermodynamics and thermoeconomics - Durmayaz, A; Sogut, OS; Sahin, B; Yavuz, H (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
The irreversibilities originating from finite-time and finite-size constraints are important in the real thermal system optimization. Since classical thermodynamic analysis based on thermodynamic equilibrium do not consider these constraints directly, it is necessary to consider the energy transfer between the system and its surroundings in the rate form. Finite-time thermodynamics provides a fundamental starting point for the optimization of real thermal systems including the fundamental concepts of heat transfer and fluid mechanics to classical thermodynamics. In this study, optimization studies of thermal systems, that consider various objective functions, based on finite-time thermodynamics and thermoeconomics are reviewed. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: finite-time thermodynamics; optimization; endoreversible; irreversible; heat engine; refrigerator; heat pump; thermoeconomics; GENERAL PERFORMANCE-CHARACTERISTICS; MAXIMUM POWER-DENSITY; HEAT-ENGINE-DRIVEN; COMBINED REFRIGERATION SYSTEM; COMBINED CARNOT CYCLE; OPTIMUM PERFORMANCE; ECOLOGICAL OPTIMIZATION; OPTIMAL CONFIGURATION; ENTROPY GENERATION; IRREVERSIBLE REFRIGERATORS; Thermodynamics; Energy & Fuels; Engineering